Art Education Based on Joyful Learning Method and Information Communication Technology at Insan Mulia School of Nature Surabaya - Idealita Ismanto (Institut Seni Indonesia Denpasar, 2018)
This article discusses joyful learning method in Insan Mulia Surabaya School of Nature and describes ICT-based art education (Information and Communication Technology) at Insan Mulia School of Nature Surabaya. This research uses qualitative approach and descriptive research type. Data collection procedure is done by observation and interview method. Data analysis activities started from the data collection stage, the reduction phase, the data presentation stage, and the conclusion drawing stage. Data validation checks are performed with source triangulation, and method triangulation. The results of the study showed that: (1) Bina Insan Muliaâ€™s school education has a learning model of joyful learning (2) ICT-based arts education (Information and Communication Technology) to make student learning activities more interesting and not monotonous.Artikel ini membahas tentang metode pedidikan joyful learning di Sekolah Alam Insan Mulia Surabaya dan mendeskripsikan pendidikan seni berbasis ICT (Information and Communication Technology) di Sekolah Alam Insan Mulia Surabaya. Penelitian ini menggunakan pendekatan kualitatif dan jenis penelitian deskriptif. Prosedur pengumpulan data dilakukan dengan metode observasi dan wawancara. Kegiatan analisis data dimulai dari tahap pengumpulan data, tahap reduksi, tahap penyajian data, serta tahap penarikan kesimpulan. Pengecekan keabsahan data dilakukan dengan triangulasi sumber, dan triangulasi metode. Hasil penelitian menunjukkan bahwa: (1) pendidikan sekolah alam Bina Insan Mulia memiliki model pembelajaran joyful learningÂ (2) pendidikan seni berbasis ICT (Information and Communication Technology) membuat kegiatan belajar siswa lebih menarik dan tidak monoton.